2007
DOI: 10.1016/j.pain.2006.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Spinal NK-1 receptor expressing neurons mediate opioid-induced hyperalgesia and antinociceptive tolerance via activation of descending pathways

Abstract: Opioids can induce hyperalgesia in humans and in animals. Mechanisms of opiate-induced hyperalgesia and possibly of spinal antinociceptive tolerance may be linked to pronociceptive adaptations occurring at multiple levels of the nervous system including activation of descending facilitatory influences from the brainstem, spinal neuroplasticity, and changes in primary afferent fibers. Here, the role of NK-1 receptor-expressing cells in the spinal dorsal horn in morphineinduced hyperalgesia and spinal antinocice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 71 publications
6
77
0
Order By: Relevance
“…We show that the administration of escalating doses of morphine triggers mechanical hypersensitivity. This is in agreement with a number of previous studies reporting the development of hypersensitivity following morphine treatment in rodents Liang et al, 2008;Liang et al, 2011;Muscoli et al, 2010;Vera-Portocarrero et al, 2007). Sensory sensitization induced by opioids has also been reported in clinical studies showing an increase in mechanical sensitivity after repeated exposure to morphine (Chu et al, 2006;Hay et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We show that the administration of escalating doses of morphine triggers mechanical hypersensitivity. This is in agreement with a number of previous studies reporting the development of hypersensitivity following morphine treatment in rodents Liang et al, 2008;Liang et al, 2011;Muscoli et al, 2010;Vera-Portocarrero et al, 2007). Sensory sensitization induced by opioids has also been reported in clinical studies showing an increase in mechanical sensitivity after repeated exposure to morphine (Chu et al, 2006;Hay et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…In the dorsal horn, GluA4 is mainly expressed at synapses of two types of projection neurons: large gephyrin-coated projection neurons in lamina I and neurokinin-1 receptor (NK1R)-positive neurons in laminae III-V (Polgar et al, 2008a;Todd et al, 2009). As the specific ablation of projection neurons expressing NK1R completely prevents morphine-induced hyperalgesia (Vera-Portocarrero et al, 2007), it is likely that the increase in GluA4 could have a role in the development of nociceptive sensitivity after morphine. This is supported by our data showing that the direct application of an anti-GluA4 antibody through patch pipette in laminae III-V neurons completely reverses morphine-induced alterations in AMPAR-mediated currents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In favor of such a model, it has been shown that ondansetron blocks OIH, as well as opioid tolerance, after spinal administration in chronic-morphine treated rats with no peripheral injury. 116 Concerns remain regarding physical dependence, addiction, adverse effects such as hyperalgesia, and dose escalation to overcome tolerance during opioid therapy. Even so, morphine will remain the gold standard opioid against which others are judged until a drug is found that produces fewer adverse effects at a dose that provides the same analgesia.…”
Section: Opioid-induced Hyperalgesiamentioning
confidence: 99%
“…Proynorphin knockout mice fail to develop neuropathic pain following peripheral nerve injury [9] and the administration of chronic opioids produces a paradoxical hypersensitivity that is dependent upon NK-1 expressing spinal cord neurons and descending facilitation [33]. The mechanism of spinal dynorphin A maintenance of neuropathic pain is not dependent on opioids receptors but requires the activation of spinal bradykinin receptors [17].…”
Section: Introductionmentioning
confidence: 99%